Ethanol concentration and calorific value of some local distilled Ethiopian alcohol (Areki): an energy potential assessment. Issue 1 (1st January 2021) - Assaye, Mebratu; Tamirat, Bimrew; Fekadu, Birlie
Abstract: This paper deals with determination of the ethanol concentration and its heating value (calorific value in local distilled Ethiopian Areki, which is extracted from Maize, Dagussa (Sorghum) and Gibto (Lupin). The primary target of this paper is assessing the energy potential of some locally produced Ethiopian alcohols by identifying the major parameters like ethanol concentration, calorific value and its acidity. The samples of Areki were prepared in one of the vending houses in Injibara Ethiopia and raw material used for their preparation was measured before preparation. The levels of ethanol concentration among the sample were determined using a UV/vis spectrophotometer. After calibrating with a standard sample (benzoic acid), the GCV of the alcohol samples was determined experimentally using an oxygen bomb calorimeter (IKA® Model C200 bomb Calorimeter). The quantitative analysis of ethanol in the sample was done by preparing an aqueous solution of ethanol to draw by means of absorbance versus concentration calibration line at a wavelength of 986 nm. The investigation shows that maximum and minimum percentages of ethanol concentration (%v/v) in the samples were found for dagim maize (50.17%) and dagim lupin Areki(26.64%), respectively. The gross calorific value of local distilled areki ranges from 6.616 MJ/kg-13.1432 MJ/kg. The highest GCV was obtained by dagim maize alcohol due to the higher ethanol content and dagim lupin alcohol with a small ethanol concentration has the lowest GCV. According to the findings, dagim alcohols extracted from sorghum and maize have high potential energy and can be blended with other fossil fuels with little purification.